DEFORMASITORII DALAM PEMBUATAN MEJA MAKAN DENGAN ORNAMEN JEPARA SEBAGAI UNSUR HIAS - Anisatun Nasikah; Gunawan Mohammad (SULUH: Jurnal Seni Desain Budaya, 2020)
The loading of dining tables and chairs which takes the basic idea of the Japanese torii gate aims to provide knowledge to the general public about the local wisdom of the Japanese state by combining local wisdom in Jepara, namely Jepara carving (Jepara Ornaments). The activity of eating together at the dining table is very important to train family discipline, especially for children. Apart from the functional point of view, it also has a psychological effect on the user. The making of dining tables and chairs combines the local wisdom of the Japanese state with the local wisdom of the city of Jepara. The results of the design of dining tables and chairs are the uniqueness of the dining table and chairs, which are different from other designs. With the deformation technique of the Japanese torii gate, namely by changing the style, position and dimensions of the torii form elements but without leaving the original elements of the Japanese torii gate. In addition, dining tables and chairs are designed by applying Jepara ornaments as traditional decorative elements into modern-style furniture products.